2013
DOI: 10.1016/j.rgmx.2013.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Early life events predispose the onset of childhood functional gastrointestinal disorders

Abstract: Early events may play an important role in the complex pathogenesis of functional gastrointestinal conditions. Timely intervention may have a critical impact on the prevention of this group of chronic incapacitating conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 77 publications
0
30
0
5
Order By: Relevance
“…It has been reported that at least one of two infants display one or more FGIDs, such as functional constipation or infantile colic, or related signs and symptoms such as hard stools or excessive crying . Even though FGIDs are mostly seen as benign in nature, and usually resolve over time, these may constitute early traumatic events that cause appreciable distress to infants and parents, with pending long‐term consequences for the well‐being of both . Considering the high incidence and impact of early‐life FGIDs, their prevention would be preferable to their treatment, with the implication that nutritional solutions would be preferable to pharmacological interventions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that at least one of two infants display one or more FGIDs, such as functional constipation or infantile colic, or related signs and symptoms such as hard stools or excessive crying . Even though FGIDs are mostly seen as benign in nature, and usually resolve over time, these may constitute early traumatic events that cause appreciable distress to infants and parents, with pending long‐term consequences for the well‐being of both . Considering the high incidence and impact of early‐life FGIDs, their prevention would be preferable to their treatment, with the implication that nutritional solutions would be preferable to pharmacological interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Functional gastrointestinal disorders (FGID) are characterized by the presence of chronic or recurrent digestive symptoms without an underlying identifiable structural or biochemical abnormality . Bonilla & Saps reviewed the impact of early‐life events and the development of FGID and found that early gastrointestinal inflammation, including acute bacterial gastroenteritis and CMPA, increased the risk of developing FGID . The suggestion that early‐life CMPA increases the risk was based on 2 studies, one on children aged 10 years, with a history of CMPA diagnosed at less than 1 year of age.…”
Section: Functional Gastrointestinal Disordermentioning
confidence: 91%
“…92 Bonilla & Saps reviewed the impact of early-life events and the development of FGID and found that early gastrointestinal inflammation, including acute bacterial gastroenteritis and CMPA, increased the risk of developing FGID. 93,94 The suggestion that early-life CMPA increases the risk was based on 2 studies, one on children aged 10 years, with a history of CMPA diagnosed at less than 1 year of age. That study found that 45% of children (n = 56) had gastrointestinal symptoms when using milk and milk products freely.…”
Section: Fun C Tional G a S Trointe S Tinal Disordermentioning
confidence: 99%
“…proposed that various mechanisms such as genetics, early life events, environmental, gastrointestinal and psychosocial factors act together in a complex interplay ultimately resulting in an alteration to the gut-brain axis 10,11,12,13,14,15,16 . Afferent signals from the gastrointestinal tract transmitted via the pain pathways are subsequently amplified and the patient's perception of painful stimuli is in turn enhanced 17 .…”
Section: Pathophysiologymentioning
confidence: 99%